On some weak conditions of commutativity in common fixed point theorems - M. Imdad; M. S. Khan; S. Sessa (International Journal of Mathematics and Mathematical Sciences)
We generalize common fixed point theorems of Fisher and Sessa in complete metric spaces, using some conditions of weak commutativity between a set-valued mapping and a single-valued mapping. Suitable examples prove that these conditions do not imply each of the others.